A Feature-Based Fragile Watermarking of Color Image for Secure E-Government Restoration - Lusia Rakhmawati; Wirawan Wirawan; Suwadi Suwadi; Titiek Suryani; E Endroyono (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
this research developed a method using fragile watermarking technique for color images to achieve secure e-government tamper detection with recovery capability. Before performing the watermark insertion process, the RGB image is converted first into YCbCr image. The watermark component is selected from the image feature that approximates the original image, in which the chrominance value features as a watermark component. For a better detection process, 3-tuple watermark, check bits, parity bits, and recovery bits are selected. The average block in each 2 x 2 pixels is selected as 8 restoration bits of each component, the embedding process work on the pixels by modifying the pixels value of three Least Significant Bit (LSB) . The secret key for secure tamper detection and recovery, transmitted along with the watermarked image, and the algorithm mixture is used to extract information at the receiving end. The results show remarkably effective to restore tampered image.